Enhancing Security Using ECDSA-Based Hardware Security Module with DS28E38 Secure Data Authentication IC - Istiyanto, Jazi Eko; Natan, Oskar; Augoestien, Nia Gella; Peradeniya, Irfansyah; Rachman, Syauqi Giffari; Putri, Mellia; Amael, Joshua Tito; Sari, Rifda Hakima (International Journal of Integrated Engineering, 2025)
The increasing integration of technology across diverse sectors such as manufacturing, logistics, healthcare, and smart infrastructure has enhanced operational efficiency and introduced significant cybersecurity vulnerabilities due to open networks and automatic technology. This research addresses these risks by developing a verification system using the integrated circuit (IC) security DS28E38, which employs Elliptic Curve Cryptography (ECC) to keep data integrity. The key innovation lies in combining physically unclonable function (PUF)-based authentication with the Elliptic Curve Digital Signature Algorithm (ECDSA), providing a resilient mechanism for device identity verification and protection against cyber threats. The research also includes a comprehensive performance evaluation, considering metrics such as time efficiency, memory utilization, power consumption, and resilience against simulated cyberattacks, demonstrating that the proposed system significantly enhances cybersecurity while preserving operational performance.